Recent Topics in Economic Research – Feature Papers for Cerebrating the 10th Anniversary of Economies - Fendel, Ralf; Czudaj, Robert; Anwar, Sajid (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In 2023, Economies celebrates its 10th anniversary. Thanks to the incredible support from all of you, the journal has developed into a well-respected academic journal. Economies has been included in several journal rankings, has a decent and growing number of submissions by well-known experts, and obtains very satisfactory citation scores given its young age. We acknowledge these achievements with a dedicated Special Issue. Therefore, researchers from all areas of economic research have been invited to submit their contributions to this Special Issue. The Special Issue is titled "Recent Topics in Economic Research" and covers a broad range of topics that are currently at the forefront of economics research and that are within Economies' scope. This includes original research papers as well as comprehensive review papers on topics of actual importance in economics.